Controlling methicillin-resistant Staphylococcus aureus (MRSA) in a hospital and the role of hydrogen peroxide decontamination: an interrupted time series analysis. Issue 4 (19th April 2014) - Mitchell, Brett G; Digney, Wilhelmine; Locket, Phil; Dancer, Stephanie J
Abstract : Objectives: The impact of surface disinfection versus detergent cleaning on healthcare associated infection rates remains unresolved. We aimed to evaluate the efficacy of hydrogen peroxide (HP) decontamination against methicillin-resistant Staphylococcus aureus (MRSA). Design: Single centred retrospective before and after study design. Setting: Launceston General Hospital, Tasmania, Australia. Participants: Patients with MRSA infection or colonisation. Interventions: Rooms occupied by patients with MRSA infection or colonisation were cleaned following discharge with either detergent or HP. Main outcome measures: MRSA room contamination following cleaning; new MRSA acquisition in patients. Results: Over 3600 discharge cleans were completed, with more than 32 600 environmental swabs processed. MRSA was isolated from 24.7% rooms following detergent cleaning and from 18.8% of rooms after HP (p<0.001). The incidence of MRSA acquisition reduced from 9.0 to 5.3 per 10 000 patient days in detergent and disinfectant arms, respectively (p<0.001). Conclusions: Use of HP disinfection led to a decrease in residual MRSA contamination in patient rooms compared with detergent. It may also have encouraged the reduction in patient MRSA acquisition despite several confounders including staff feedback on terminal cleaning, additional MRSA screening and quicker laboratory methods. Infection control is best served by concurrent interventions targeting both the patient and healthcare environment.